Highly Efficient Ammonia Synthesis Electrocatalyst: Single Ru Atom on Naturally Nanoporous Carbon Materials (Adv. Theory Simul. 5/2018). Issue 5 (3rd May 2018) - Cao, Yongyong; Gao, Yijing; Zhou, Hu; Chen, Xianlang; Hu, Hui; Deng, Shengwei; Zhong, Xing; Zhuang, Guilin; Wang, Jianguo
Abstract : The key factor of electrocatalytic ammonia synthesis is to search for highly efficient catalysts. In article number1800018, Jianguo Wang and co‐workers systemically study the stability and electrochemical reduction of N2 to NH3 of Ru1 @T‐C2 N, Ru1 @T‐C3 N4, and Ru1 @γ‐graphynes. These catalysts have excellent stability due to the high cohesive energy and good reactivity for electrocatalytic NRR by means of density functional calculations and Gibbs free energies analysis. The new type of catalysts theoretically predicted may open a door for experimental studies.